2022
DOI: 10.3390/ijerph19126978
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trace Metals Contamination, Species Distribution and Mobility in River Sediments Using EDTA Extraction

Abstract: The impact of the ethylenediaminetetraacetic acid (EDTA) on speciation image of selected trace metals (Zn, Cd, Cu, Pb) in bottom sediments was determined. The influence on the effectiveness of metal removal of extraction multiplicity, type of metal, extraction time and concentration of EDTA were analyzed. With the increase of extraction multiplicity, the concentration of EDTA and contact time, the efficiency of trace metals leaching increased. The speciation analysis revealed that EDTA not only leached metals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It was also demonstrated that the degree of metal immobilization depends on their chemical properties, chemical composition of ash and the ambient environment of the slurry. The heavy metals chosen for the tests (Cu, Cd, Zn, Ni and Pb) exhibit the ease of precipitating from sewage to the soil and groundwaters, as well as high toxicity (Wojtkowska and Bogacki, 2012). Therefore, these metals can be divided into two groups, namely, semivolatile (Pb, Cd) and non-volatile (Zn, Cu, Ni) metals.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that the degree of metal immobilization depends on their chemical properties, chemical composition of ash and the ambient environment of the slurry. The heavy metals chosen for the tests (Cu, Cd, Zn, Ni and Pb) exhibit the ease of precipitating from sewage to the soil and groundwaters, as well as high toxicity (Wojtkowska and Bogacki, 2012). Therefore, these metals can be divided into two groups, namely, semivolatile (Pb, Cd) and non-volatile (Zn, Cu, Ni) metals.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many models were commonly used to describe the kinetic chemical behavior of heavy metals, particularly around mines (Camizuli et al, 2014;Fangueiro et al, 2005;Gismera et al, 2004;Wojtkowska and Bogacki, 2022). The first-order kinetic model has been commonly used and assumed to have good dynamic significance:…”
Section: Kinetic Modelling and Data Processingmentioning
confidence: 99%
“…Sediments are a crucial part of rivers and lakes. During several physical and chemical processes, suspended solids and different ions in the water are adsorbed and enriched in sediments in river channels, reducing the contamination in water sediments [ 1 , 2 , 3 ]. This can objectively show the area’s water quality.…”
Section: Introductionmentioning
confidence: 99%